Changes in Physical Properties of the Nankai Trough Megasplay Fault Induced by Earthquakes, Detected by Continuous Pressure Monitoring. Issue 2 (23rd February 2018) - Kinoshita, C.; Saffer, D.; Kopf, A.; Roesner, A.; Wallace, L. M.; Araki, E.; Kimura, T.; Machida, Y.; Kobayashi, R.; Davis, E.; Toczko, S.; Carr, S.
Abstract: One primary objective of Integrated Ocean Drilling Program Expedition 365, conducted as part of the Nankai Trough Seismogenic Zone Experiment, was to recover a temporary observatory emplaced to monitor formation pore fluid pressure and temperature within a splay fault in the Nankai subduction zone offshore SW Honshu, Japan. Here we use a 5.3 year time series of formation pore fluid pressure, and in particular the response to ocean tidal loading, to evaluate changes in pore pressure and formation and fluid elastic properties induced by earthquakes. Our analysis reveals 31 earthquake‐induced perturbations. These are dominantly characterized by small transient increases in pressure (28 events) and decreases in ocean tidal loading efficiency (14 events) that reflect changes to formation or fluid compressibility. The observed perturbations follow a magnitude‐distance threshold similar to that reported for earthquake‐driven hydrological effects in other settings. To explore the mechanisms that cause these changes, we evaluate the expected static and dynamic strains from each earthquake. The expected static strains are too small to explain the observed pressure changes. In contrast, estimated dynamic strains correlate with the magnitude of changes in both pressure and loading efficiency. We propose potential mechanism for the changes and subsequent recovery, which is exsolution of dissolved gas in interstitial fluids in response to shaking. Key Points: Regional earthquakes (Mw > 5.0 and distance <1, 000 km) produce hydrological perturbations of the formation Estimated hydraulic diffusivity of the megasplay fault at Nankai is >9.1 × 10 −6 m 2 s −1 The mechanisms of hydrological perturbations can be explained by exsolution of gas from pore water